BIRD STRIKE AS A MECHANISM OF THE MOTION IN MIRCE MECHANICS - Knežević, Jezdimir (Journal of Applied Engineering Science, 2014)
Birds represent a serious, but often misunderstood, threat to aircraft. Most bird strikes do not result in any aircraft damage, but some bird strikes have led to serious accidents involving aircraft of every size. According to Bird strike Committee USA, bird and other wildlife strikes to aircraft result in over 600 million in damage to U.S. civil and military aviation each year. The lives of the crew and passengers are also at risk. Since 1988, over 200 people have been killed worldwide as a result of encounters with birds and other wildlife. Thus, this paper addresses bird strike from Mirce Mechanics point of view, which means that it is considered as a mechanism that generates a functionability event which causes the motion of a system from positive to negative functionability state. The paper provides vital information about the physical properties of most common birds that are required for predictions of their impacts on aircrafts, at the design stages as a scientific method for the evaluation of alternatives.